The Analysis of the Mid-Range Islamic Hotel Marketing Strategy - Alam, Azhar; Ratnasari, Ririn Tri; Jamil, Fadila Ainur; Ma'ruf, Aminudin (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThis paper aimed at addressing the marketing strategy performed by a mid-range Islamic hotel in Indonesia that distinguishes it from other non-sharia hotels by analyzing its marketing strategy using the SWOT analysis approach. This hotel applied Islamic principles in carrying out its marketing strategies to avoid immoral acts and fraud, and the facilities and services provided were different, which made it distinct from non-sharia hotels. Research data were obtained through interviews with six parties: managers, marketing staff, receptionists, and guests. This study also used observation to validate the data collected. The findings of the study showed that the marketing strategy undertaken by Multazam Sharia Hotel was different compared to non-sharia hotels due to feature distinctions. Regarding the results of the SWOT analysis, in SO strategy, the hotel should use its strengths to make use of the opportunity to achieve its goals. In WO, the hotel was expected to maximize the opportunity by minimizing the weakness. The ST strategy analysis revealed that this hotel needed to move fast in dealing with threats and minimize the unexpected consequences of the threats. The last, the WT strategy, Multazam sharia hotel must be careful with the weaknesses and threats it faces. If the hotel cannot make improvements in facilities and services, it may be displaced by the times.ABSTRAKStudi ini bertujuan membahas strategi pemasaran yang dilakukan oleh hotel Islam kelas menengah di Indonesia yang membedakannya dengan hotel non syariah lainnya dengan menganalisis strategi pemasarannya menggunakan pendekatan analisis SWOT. Penelitian ini merupakan penelitian lapangan yang dengan pendekatan deskriptif-kualitatif. Data penelitian diperoleh melalui observasi dan wawancara di hotel syariah Multazam. Analisis data dilakukan analisis SWOT (Strength, Opportunity, Weakness, Threats). Hasil penelitian menunjukkan bahwa strategi pemasaran yang dilakukan Hotel Multazam Syariah berbeda dengan hotel non syariah karena perbedaan fitur. Hotel ini menerapkan prinsip-prinsip Islam dalam menjalankan strategi pemasarannya untuk menghindari tindakan maksiat dan penipuan serta fasilitas dan layanan yang diberikan berbeda dengan hotel non-syariah. Mengenai hasil analisis SWOT, dalam strategi SO, hotel harus menggunakan kekuatannya untuk memanfaatkan peluang untuk mencapai tujuan hotel. Dalam WO, hotel diharapkan memaksimalkan peluang dengan meminimalkan kelemahan. Strategi ST mengungkapkan bahwa hotel ini perlu bergerak cepat dalam menghadapi ancaman dan meminimalkan konsekuensi tak terduga dari ancaman tersebut. Terakhir, strategi WT, hotel syariah Multazam harus berhati-hati dengan kelemahan dan ancaman yang dihadapinya. Jika hotel tidak dapat melakukan perbaikan fasilitas dan layanan, hotel dapat tergeser oleh waktu.